Intramedullary Implant Choice and Cost in the Treatment of Pediatric Diaphyseal Forearm Fractures. Issue 10 (October 2017) - Heare, Austin; Goral, Dawn; Belton, Matthew; Beebe, Corey; Trizno, Anastasiya; Stoneback, Jason
Abstract : Objectives: To compare outcomes and costs between titanium elastic nails (TENs), stainless steel elastic nails (SENs), and Kirschner wires (K-wires) in the treatment of pediatric diaphyseal forearm fractures with intramedullary fixation. Design: Retrospective cohort study. Setting: Level 1 Pediatric Trauma Center. Patients/Participants: A total of 100 patients (65 male and 35 female) younger than 18 years with diaphyseal forearm fractures treated with intramedullary fixation were included in the study. Intervention: Patients received single or both bone intramedullary fixation with either TENs, SENs, or K-wires. Main Outcome Measurements: Time to radiographic union, complication rate, surgical time, and average cost per implant. Results: One hundred patients were included in the study. Thirty-one patients were treated with TENs, 30 with SENs, and 39 with K-wires. No significant difference in time to radiographic union, complication rate, or surgical time was found between the 3 types of fixation. Average time to union was 9.4 ± 5.4 weeks, and complication rate was 12.9% for TENs, 10.0% for SENs, and 12.8% for K-wires. There was a significant difference in cost per implant, with an average cost of $639, $172, and $24 for TENs, SENs, and K-wires, respectively ( P < 0.001). Conclusions: This study demonstrates no difference between TENs, SENs, and K-wires in the treatment of pediatric diaphyseal forearm fractures with regards to outcome, time to union, surgical time, or complication rates. Given the significant cost difference between these implants, we recommend that surgeons consider modifying their implant selection to help mitigate cost. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.